Association between arterial stiffness and a change in the expression of the apoptotic marker of caspase-3 in patients with diabetes mellitus type 2 and overweight or obesity - Soloviuk, O. A.; Soloviuk, O. O.; Солов'юк, Олександр Олегович (My University, 2020)
Purpose. To reveal the presence and nature of the relationship between arterial stiffness and expression in patients with diabetes mellitus type 2 and overweight or obesity.
Keywords: тези доповідей